High-resolution ultrasonography for early diagnosis of neural impairment in seropositive leprosy household contacts. - Andrea De Martino Luppi; Guilherme Emilio Ferreira; Denis Luiz Prudêncio; Douglas Eulálio Antunes; Lúcio Araújo; Diogo Fernandes Dos Santos; Marcello Henrique Nogueira-Barbosa; Isabela Maria Bernardes Goulart (PLoS ONE, 2023)
Leprosy household contacts (HC) represent a high-risk group for the development of the disease. Anti-PGL-I IgM seropositivity also increases the risk of illness. Despite significant advances in leprosy control, it remains a public health problem; and early diagnosis of this peripheral neuropathy represents one of the main goals of leprosy programs. The present study was performed to identify neural impairment in leprosy HC by analyzing differences in high-resolution ultrasonographic (US) measurements of peripheral nerves between leprosy HC and healthy volunteers (HV). Seventy-nine seropositive household contacts (SPHC) and 30 seronegative household contacts (SNHC) underwent dermato-neurological examination and molecular analysis, followed by high-resolution US evaluation of cross-sectional areas (CSAs) of the median, ulnar, common fibular and tibial nerves. In addition, 53 HV underwent similar US measurements. The US evaluation detected neural thickening in 26.5% (13/49) of the SPHC and only in 3.3% (1/30) among the SNHC (p = 0.0038). The CSA values of the common fibular and tibial nerves were significantly higher in SPHC. This group also had significantly greater asymmetry in the common fibular and tibial nerves (proximal to the tunnel). SPHC presented a 10.5-fold higher chance of neural impairment (p = 0.0311). On the contrary, the presence of at least one scar from the BCG vaccine conferred 5.2-fold greater protection against neural involvement detected by US (p = 0.0184). Our findings demonstrated a higher prevalence of neural thickening in SPHC and support the role of high-resolution US in the early diagnosis of leprosy neuropathy. The combination of positive anti-PGL-I serology and absence of a BCG scar can identify individuals with greater chances of developing leprosy neuropathy, who should be referred for US examination, reinforcing the importance of including serological and imaging methods in the epidemiological surveillance of leprosy HC.